2020
DOI: 10.2147/ott.s275135
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA SNHG6 Inhibits Apoptosis by Regulating EZH2 Expression via the Sponging of MiR-101-3p in Esophageal Squamous-Cell Carcinoma</p>

Abstract: Background: The long non-coding RNA (lncRNA) SNHG6 was significantly upregulated in esophageal squamous-cell carcinoma (ESCC), and it promoted ESCC cell proliferation, invasion, and migration. However, the effects of SNHG6 on cell apoptosis and the corresponding underlying mechanisms have not yet reported. Methods: Apoptosis was detected by flow cytometric analysis. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting were used for mRNA and protein quantification, respectively. A luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…The latest research showed that an inhibitor of EZH2 activity-GSK343 could significantly promote the differentiation of hematopoietic stem cells (HPCs) into MDSCs in the presence of granulocytemacrophage colony-stimulating factors (GM-CSF) and interleukin-6 (IL-6) in vitro [8]. In addition, the involvement of lncRNA Snhg6 in regulating EZH2 has also been reported [6,9]. So we speculate that lncRNA Snhg6 may regulate the differentiation of MDSCs through EZH2.…”
Section: To the Editormentioning
confidence: 85%
“…The latest research showed that an inhibitor of EZH2 activity-GSK343 could significantly promote the differentiation of hematopoietic stem cells (HPCs) into MDSCs in the presence of granulocytemacrophage colony-stimulating factors (GM-CSF) and interleukin-6 (IL-6) in vitro [8]. In addition, the involvement of lncRNA Snhg6 in regulating EZH2 has also been reported [6,9]. So we speculate that lncRNA Snhg6 may regulate the differentiation of MDSCs through EZH2.…”
Section: To the Editormentioning
confidence: 85%
“…Our previous research also revealed that EZH2 was upregulated in samples afflicted by EC and EZH2 was confirmed as an oncogene in esophageal cancer via biological experiments (22). Recent studies have revealed that EZH2 promoted chemotherapeutic drug resistance in numerous cancers (23,24).…”
Section: Introductionmentioning
confidence: 88%
“…Small nucleolar RNA host genes (SNHGs), for instance, play extremely important regulatory roles in ESCC. Specifically, lncRNA-SNHG6 can inhibit ESCC cell apoptosis by targeting miR-101-3p to regulate Enhancer of zeste homolog 2 (EZH2) (15). Furthermore, SNHG5 can inhibit the epithelial-mesenchymal transition process of ESCC cells through ubiquitination and degradation of metastasisassociated protein 2 (MTA2) (16).…”
Section: Discussionmentioning
confidence: 99%